2017
DOI: 10.1080/00224545.2017.1327405
|View full text |Cite|
|
Sign up to set email alerts
|

Kill or cure? Different types of social class identification amplify and buffer the relation between social class and mental health

Abstract: The present research investigated different types of social class identification as moderators of the negative relation between social class and mental health problems. Psychology undergraduates (N = 355) completed an online survey that included measures of social class, mental health and well-being, and three aspects of social class identification: importance of identity, salience of identity, and perceived self-class similarity. Perceived self-class similarity buffered the negative association between social… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…These tests did not yielded any significant interaction effects (ps ≥ 0.206). Hence, we did not replicated Rubin and Stuart's (2018) initial findings. These null results may have occurred due to (a) Type I errors in the original study, (b) Type II errors in the current study due to less powerful measures, or (c) a genuine change in the results that have been caused by changes in the methodology between the two studies.…”
Section: Participantsmentioning
confidence: 56%
See 1 more Smart Citation
“…These tests did not yielded any significant interaction effects (ps ≥ 0.206). Hence, we did not replicated Rubin and Stuart's (2018) initial findings. These null results may have occurred due to (a) Type I errors in the original study, (b) Type II errors in the current study due to less powerful measures, or (c) a genuine change in the results that have been caused by changes in the methodology between the two studies.…”
Section: Participantsmentioning
confidence: 56%
“…In addition, most participants indicated that they were full-time 1 As indicated in our As.Predicted preregistered research protocol, we also tested a separate set of hypotheses that (a) higher levels of perceived self-to-group similarity (e.g., "I am quite similar to other women in my job") and in-group ties (e.g., "I feel strong ties with other women in my job") would reduce the negative association between women's low status minority position and their mental health and job satisfaction, whereas (b) higher levels of perceived importance of the female worker identity (e.g., "Being a woman in my job is an important part of my self-image") would increase the size of these negative associations. These hypotheses were based on Rubin and Stuart's (2018) proposal that different types of social identification amplify and buffer the relation between membership in high and low status groups and mental health. Due to an error, we did not include a measure of ingroup ties in the current survey.…”
Section: Participantsmentioning
confidence: 99%
“…Adolescents regard family assets, family lifestyle, parents' occupations, and parents' education levels as important factors in determining their subjective social family class (SFC) [3]. The SSS is associated with the individuals' health and well-being, even when adjusted for the objective socioeconomic status in previous studies conducted on adults [4,5] and adolescents [1]. In Korean adults, the SSS was found to be associated significantly with psychological problems, including suicidal ideation, depression, and psychological pressure [4].…”
Section: Introductionmentioning
confidence: 99%
“…These tests did not yielded any significant interaction effects (ps ≥ .206). Hence, we did not replicated Rubin and Stuart's (2018) initial findings. These null results may have occurred due to (a) Type I errors in the original study, (b) Type II errors in the current study due to less powerful measures, or (c) a genuine change in the results that have been caused by changes in the methodology between the two studies.…”
Section: Referencesmentioning
confidence: 56%
“…As indicated in our As.Predicted preregistered research protocol, we also tested a separate set of hypotheses that (a) higher levels of perceived self-to-group similarity (e.g., "I am quite similar to other women in my job") and in-group ties (e.g., "I feel strong ties with other women in my job") would reduce the negative association between women's low status minority position and their mental health and job satisfaction, whereas (b) higher levels of perceived importance of the female worker identity (e.g., "Being a woman in my job is an important part of my self-image") would increase the size of these negative associations. These hypotheses were based on Rubin and Stuart's (2018) proposal that different types of social identification amplify and buffer the relation between membership in high and low status groups and mental health. Due to an error, we did not include a measure of ingroup ties in the current survey.…”
Section: Referencesmentioning
confidence: 99%